2009
DOI: 10.1007/s11666-009-9329-y
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Powder Injection in the High-Pressure Cold Spray Process

Abstract: High-pressure cold spray process is a relatively new coating process that uses high-velocity powder particles to form coatings. One of the requirements for this process is to inject the particles to be sprayed into a prenozzle chamber where both the particles and the powder feed gas are entrained into the primary gas stream. In this study, we investigated the effects of powder injection on coating formation through both experimental studies and computational simulations. Several issues related to powder inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The standard k-e turbulence model is utilized to capture the turbulent flow features because it can save the computational time considerably, and the calculation converges easily. The choice is made following the previous numerical studies on the supersonic jet flow in CS ( Ref 22,23). The non-equilibrium wall function is chosen for the near-wall flow treatment because of its great capability to deal with the large pressure gradient in the impinging jet.…”
Section: Methodsmentioning
confidence: 99%
“…The standard k-e turbulence model is utilized to capture the turbulent flow features because it can save the computational time considerably, and the calculation converges easily. The choice is made following the previous numerical studies on the supersonic jet flow in CS ( Ref 22,23). The non-equilibrium wall function is chosen for the near-wall flow treatment because of its great capability to deal with the large pressure gradient in the impinging jet.…”
Section: Methodsmentioning
confidence: 99%
“…However, particularly the dispersion of the particles was not captured sufficiently. Additionally, Han et al (2009) showed that the deposition strongly depends on the particle injection process. These aspects represent another direct link between the geometry and the deposition efficiency.…”
Section: Coupled Simulationmentioning
confidence: 99%
“…Cold spraying technology is divided into low pressure cold spraying [2][3][4][5][6][7] and high pressure cold spraying [8][9][10][11][12][13]. High pressure cold spraying technology use heated high pressure gas in low temperature to change its kinetic energy into heat energy when the solid particles impact substrate and surface of coating material, thus forming a layer of almost impermeable coating [14].But in the process of application, the cold high pressure spraying has a lot of shortcomings,because the requirements for pressure (minimum to 15 atmospheres) lead to the stopping of large equipment and reducing the security of use.…”
Section: Introductionmentioning
confidence: 99%